Application of POC fertilization from organic waste and humic acid on the growth and production of sweet corn (Zea mays L. Saccharata sturt) - Helilusiatiningsih, Nunuk; Syahara, Muhammad Alwi (AGROMIX, 2024)
Introduction: Sweet corn in Indonesia was the main commodity after rice, and it was useful for food, the snack processing industry, semi-finished ingredients, side dishes, and animal feed. Problems with sweet corn farming include limited land, inappropriate cultivation technology, expensive superior seeds, insufficient water availability, fertilizers and pesticides that do not meet needs, as well as expensive and difficult labor, and competition with other commodities. The quality of the corn was that the husk was bright green and slightly moist, the sweet corn tassels were light brown and moist, and the grain texture was dense. The research aimed to analyze the effect of adding humic acid and POC on the growth and yield of sweet corn. Methods: The experimental design was RAKF. The first factor was humic acid (A) consisting of 4 levels: control, 5 kg/ha, 10 kg/ha, and 15 kg/ha. The second factor is POC (P) consisting of 5 levels: control, 60 ml/l, 90 ml/l, 120 ml/l, and 150 ml/l so there are 20 experimental combinations. Analysis used the F count test, 5% BNT test, and 5% DMRT test. Results: In the analysis of plant height, number of leaves, and weight of corn with and without husks, the best combination was A3P4.The P4 level (150 ml/L) has the highest level of sweetness but is not significantly different, the degree of sweetness was 16.25 brix. Addition of humic acid at a concentration of 15 kg/Ha. Produces a sweetness degree of 18.35 brix. Conclusion: The results of the study indicated a significant influence from the combination of treatments, as well as an interaction between the experimental treatments. The most effective combination was A3P4, which involved a humic acid concentration of 15 kg/ha and a POC dose of 150 ml/L. This combination yielded the best results for the tested parameters and sweetness levels.